HERVs characterize normal and leukemia stem cells and represent a source of shared epitopes for cancer immunotherapy. Issue 9 (12th July 2022) - Alcazer, Vincent; Bonaventura, Paola; Tonon, Laurie; Michel, Emilie; Mutez, Virginie; Fabres, Clémentine; Chuvin, Nicolas; Boulos, Rasha; Estornes, Yann; Maguer‐Satta, Véronique; Geistlich, Kevin; Viari, Alain; et al.
Abstract: Human endogenous retroviruses (HERVs) represent 8% of the human genome. The expression of HERVs and their immune impact have not been extensively studied in Acute Myeloid Leukemia (AML). In this study, we used a reference of 14 968 HERV functional units to provide a thorough analysis of HERV expression in normal and AML bone marrow cells. We show that the HERV retrotranscriptome accurately characterizes normal and leukemic cell subpopulations, including leukemia stem cells, in line with different epigenetic profiles. We then show that HERV expression delineates AML subtypes with different prognoses. We finally propose a method to select and prioritize CD8 + T cell epitopes derived from AML‐specific HERVs and we show that lymphocytes infiltrating patient bone marrow at diagnosis contain naturally occurring CD8 + T cells against these HERV epitopes. We also provide in vitro data supporting the functionality of HERV‐specific CD8 + T‐cells against AML cells. These results show that HERVs represent an important source of genetic information that can help enhancing disease stratification or biomarker identification and an important reservoir of alternative tumor‐specific T cell epitopes relevant for cancer immunotherapy. Abstract : Normal and leukemia cells can be characterized by their Human Endogenous Retroviruses expression profile. This major source of genetic information can be used to enhance disease stratification or identify alternative tumor‐specific T‐cell epitopes relevant for cancer immunotherapy.